Comorbidity in context : Part 1. Medical considerations around HIV and tuberculosis during the COVID-19 pandemic in South Africa - Moodley, K.; Boswell, M.T.; Nienaber, A.G.; Rossouw, T.M. (South African medical journal, 2020)
Infectious diseases pandemics have devastating health, social and economic consequences, especially in developing countries such as South Africa. Scarce medical resources must often be rationed effectively to contain the disease outbreak. In the case of COVID-19, even the best-resourced countries will have inadequate intensive care facilities for the large number of patients needing admission and ventilation. The scarcity of medical resources creates the need for national governments to establish admission criteria that are evidence-based and fair. Questions have been raised whether infection with HIV or tuberculosis (TB) may amplify the risk of adverse COVID-19 outcomes and therefore whether these conditions should be factored in when deciding on the rationing of intensive care facilities. In light of these questions, clinical evidence regarding inclusion of these infections as comorbidities relevant to intensive care unit admission triage criteria is investigated in the first of a two-part series of articles. There is currently no evidence to indicate that HIV or TB infection on their own predispose to an increased risk of infection with SARS-CoV-2 or worse outcomes for COVID-19. It is recommended that, as for other medical conditions, validated scoring systems for poor prognostic factors should be applied. A subsequent article examines the ethicolegal implications of limiting intensive care access of persons living with HIV or TB.